Absolute abundances of palynological organic matter (POM) of sediment core S05B from Mar Piccolo, Southern Italy - Niccolini, Gabriele; Bertini, Adele; Degl'Innocenti, Niccolò; Lisco, Stefania; Moretti, Massimo; Scardino, Giovanni; Mastronuzzi, Giuseppe (PANGAEA, 2024)
The palynological organic matter dataset was obtained from the S05B core retrieved in the Mar Piccolo, a semi-enclosed marine basin located in the Central Mediterranean. The palynological organic matter analyses were conducted on 41 samples (0,08-29,49 m), focusing on both structured and amorphous palynological organic matter. These analyses performed describe the paleoenvironmental and landscape changes during the last ~12,000 years, with particular reference to rapid Holocene climate events, such as the 8.2 and 4.2 ka BP events, and the impact of human activities. The palynological organic matter dataset (both structured and amorphous components) was obtained from eight surface sediment samples collected in the Mar Piccolo, a semi-enclosed marine basin located in the Central Mediterranean. These samples were retrieved using a grab sampler on December 10, 2022. As the Mar Piccolo is considered one of the most polluted basins in Europe, these analyses were carried out to evaluate the effects of human activity on the deposition of palynological organic matter.
Keywords: anoxia; Holocene; Mediterranean; organic matter; palynology; palynomorphs; Taranto Mare Piccolo